Modification in mitochondrial function is associated with the FADS1 variant and its interaction with alpha-linolenic acid-enriched diet - an exploratory study - Vaittinen, Maija; Ilha, Mariana; Sehgal, Ratika; Lankinen, Maria A.; Ågren, Jyrki; Käkelä, Pirjo; Virtanen, Kirsi A.; Laakso, Markku; Schwab, Ursula; Pihlajamäki, Jussi (Elsevier, 2025)
Fatty acid desaturase (FADS1) variant-rs174550 strongly regulates polyunsaturated fatty acid (PUFA) biosynthesis. Additionally, the FADS1 has been shown to be related to mitochondrial function. Thus, we investigated whether changes in mitochondrial function are associated with the genetic variation in FADS1 (rs174550) in human adipocytes isolated from individuals consuming diets enriched with either dietary alpha-linolenic (ALA) or linoleic acid (LA). Two cohorts of men homozygous for the genotype of FADS1 (rs174550) were studied: FADSDIET2 dietary intervention study with ALA- and LA-enriched diets and Kuopio Obesity Surgery study (KOBS), respectively. We could demonstrate that differentiated human adipose-derived stromal cells from subjects with the TT genotype had higher mitochondrial metabolism compared with subjects with the CC genotype of FADS1-rs174550 in the FADSDIET2. Responses to PUFA-enriched diets differed between the genotypes of FADS1-rs174550, showing that ALA, but not LA, -enriched diet stimulated mitochondrial metabolism more in subjects with the CC genotype when compared with subjects with the TT genotype. ALA, but not LA, proportion in plasma phospholipid fraction correlated positively with adipose tissue mitochondrial-DNA amount in subjects with the CC genotype of FADS1-rs174550 in the KOBS. These findings demonstrate that the FADS1-rs174550 is associated with modification in mitochondrial function in human adipocytes. Additionally, subjects with the CC genotype, when compared with the TT genotype, benefit more from the ALA-enriched diet, leading to enhanced energy metabolism in human adipocytes. Altogether, the FADS1-rs174550 could be a genetic marker to identify subjects who are most suitable to receive dietary PUFA supplementation, establishing also a personalized therapeutic strategy to improve mitochondrial function in metabolic diseases.